Peran Suami dalam Perawatan Kehamilan Istri di Kelurahan Mulyorejo - Imroatul Hasanah; Nurul Fitriyah (Universitas Airlangga, 2018)
National health development strategy has resulted in improved public health status. One of indicators public health is Maternal Mortality Rate (MMR). Maternal Mortality Rate is a health problem that still many still occur in Indonesia. One factor contributing to high incidence of maternal mortality is lack of antenatal care attention. Antenatal care is an important and mandatory thing done by mother during pregnancy because it can maintain the health of mother and fetus until the birth process. Antenatal care can identify the risk of complications experienced by the mother during pregnancy. Participation of antenatal care not only from wife, but participation of pregnancy care can also be from support of the closest person is husband. Husband role is needed in the care of pregnancy because wife needs a lot of biological and psychological support. Purpose of research is to know characteristics husband to antenatal care in Mulyorejo. Type of research is descriptive with cross sectional using qualitative method. Techniques data collection using questionnaires with the sample number of respondents is 20 husbands who have pregnant wives. Respondent is taken from Mulyorejo Health Center data. Analysis Method with descriptive statistics by displaying the frequency in the form of tables showing the categories of characteristics husband. This study lasted for one month in October to November 2017. The results showed that characteristics of husbands in antenatal care in Mulyorejo is sufficient category. Knowledge of husband is 14 people (70%), husband attitude is 10 people (50%), and husband behavior is 13 people (65%).